Functional Connectivity of Anterior Insula Predicts Recovery of Patients With Disorders of Consciousness - Zhang, Li; Luo, Lunjie; Zhou, Zhen; Xu, Kaibin; Zhang, Lijuan; Liu, Xiaoyan; Tan, Xufei; Zhang, Jie; Ye, Xiangming; Gao, Jian; Luo, Benyan (Frontiers in Neurology, 2018)
Objective: We hypothesize that the insula plays an important role in the maintenance of awareness. Here, we explored the functional connectivity alterations of the insula in patients with disorders of consciousness (DOC) and their potential correlation with clinical outcomes. Methods: A total of 12 participants(8 patients with DOC and 4 age matched healthy controls) were recruited for this study. Each patient with DOC underwent rest-state functional MRI (rs-fMRI) scan and a standardized Coma Recovery Scale-Revised (CRS-R) assessment on the same day. We split the patients into two subgroups according to the prognosis: those who emerged from a minimally conscious state (Rec group, n=4) and those who remained in an unresponsive wakefulness syndrome (UWS) (Unrec group, n=4). RS-fMRI scan and CRS-R assessment were repeated for all patients. We used the seed-based fMRI analysis, with 12 seeds for the bilateral insula, to investigate functional connectivity alterations before and after the recovery of consciousness as well as the difference in the Rec, Unrec and Con groups. Correlations with CRS-R were probed with the Spearman correlation coefficient. Results: Functional connectivity between the ventral agranular insula (vIa) and the precuneus (PCU) was found to become stronger as consciousness recovered (p＜0.005), with no change in patients remained in UWS (p＞0.05). The strength of vIa-to-PCU functional connectivity was positively correlated with CRS-R score (Spearman r=0.933, p＜0.001). Conclusions: Our findings indicate that the recovery of consciousness is associated with increased vIa-PCU connectivity. This may shed new light on the role of the insula in the maintenance of human consciousness. Moreover, dynamic variations of vIa-PCU connectivity may be a potential hallmark in the outcome prediction of DOC patients.